2009
DOI: 10.1007/s11164-009-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial concentration of LASs on the rates of sonochemical degradation and cavitation efficiency

Abstract: The effect of initial concentration of linear alkylbenzene sulfonate (LAS: p-octylbenzene sulfonate (LAS C 8 ), p-nonylbenzene sulfonate (LAS C 9 ), p-dodecylbenzene sulfonate (LAS C 12 )) on the rate of sonochemical degradation was investigated over a wide concentration range under Ar atmosphere by 200 kHz ultrasonic irradiation. The degradation rate of each LAS increased with increasing initial concentration of LAS and then started to decrease with the different behavior depending on the types of LASs. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It has previously been reported that micelle formation can reduce the cavitation efficiency [20] , [21] . In addition, based on the clear relationship between the maximum degradation rate and cmc for LASs, we suggested that micelles formed in the interfacial region of the cavity by accumulation of the anionic surfactant even when the concentration was less than the cmc and reduced the cavitation efficiency [25] . We then investigated the relation between the maximum degradation rate and the cmc for surfactants with different charge types.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…It has previously been reported that micelle formation can reduce the cavitation efficiency [20] , [21] . In addition, based on the clear relationship between the maximum degradation rate and cmc for LASs, we suggested that micelles formed in the interfacial region of the cavity by accumulation of the anionic surfactant even when the concentration was less than the cmc and reduced the cavitation efficiency [25] . We then investigated the relation between the maximum degradation rate and the cmc for surfactants with different charge types.…”
Section: Resultsmentioning
confidence: 89%
“…3 . For comparison, the data for LAS C 9 and C 12 are also plotted [25] . If micelle formation of the surfactant reduced the cavitation efficiency, the degradation rate should reach the maximum value when the initial bulk concentration is the cmc (dashed line in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation